(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Worldwide, there is a massive implementation of integrated marketing communication (IMC). Thisliterature study aims to clarify the nature of integrated marketing communication (IMC), the significance ofIMC, and the distinction between IMC and more conventional forms of marketing communication. Insteadof focusing on the objectives of the business itself, the goal of integrated marketing communication is tomeet the demands of the customer. The process of IMC is collaborative rather than individual. Brandrecognition, consumer happiness, brand loyalty, a favorable brand image, memorable brandassociations, expanded market share, higher profits, and reduced expenses are just a few of the benefitsof integrated marketing communications. Organizational performance and reputation may besignificantly influenced by IMC. Some obstacles prevent the IMC program from being fully implemented.